180k views
5 votes
With work please!!!

f(x) = -x^4 + 5x - 4x^2

(f (2))^2

User Liliane
by
5.2k points

1 Answer

5 votes

Answer: 484

===============================================

Work Shown:

First let's compute f(2). We replace every x with 2 and then use PEMDAS to simplify

f(x) = -x^4 + 5x - 4x^2

f(2) = -(2)^4 + 5(2) - 4(2)^2

f(2) = -16 + 5(2) - 4(4)

f(2) = -16 + 10 - 16

f(2) = -6 - 16

f(2) = -22

Then we square this result to find the value of
[ f(2) ]^2


f(2) = -22\\\\\left[ f(2) \right]^2 = [ -22 ]^2\\\\\left[ f(2) \right]^2 = 484

User Mert Can Ilis
by
4.6k points